광전기화학 물분해 수소 제조 기술에서 수소화효소 엔자임 활용 - 조혜경(HYEKYUNG CHO); 정현민(HYEONMIN JUNG); 윤재경(JAEKYUNG YOON); 이광복(KWANGBOK YI); 김한성(HANSUNG KIM); 주현규(HYUNKU JOO) (한국수소 및 신에너지학회 논문집, 2022)
There is growing interest in sustainable energy sources that can reduce fossil fuel dependence and environmental pollution while meeting rapidly growing energy demands. Hydrogen have been investigated as one of the ideal alternative energies because it has relatively high efficiency without emitting pollutants. The light-sensitized enzymatic (LSE) system, which uses hydrogenase-enzymes, is one of the methods towards economically feasible system configurations that enhance the rate of hydrogen generation. Hydrogenase is an enzyme that catalyzes a reversible reaction that oxidizes molecular hydrogen or produces molecular hydrogen from protons and electrons. In this paper, utilization of [NiFe]-hydrogenase (from Pyrococcus furiosus) in photoelectrochemical hydrogen production system such as handling, immobilization, physicochemical and electrochemical analysis, process parameters, etc. was introduced.